Peran Media Sosial Dimasa Pandemi untuk Kemajuan Perekonomian Di Masyarakat - Novita Risnawati (Universitas Nusantara PGRI Kediri, 2021)
Social media is now a daily food. Starting from the children to the older generation can not be separated from the existence of social media. The existence of social media makes it easier for us to obtain and convey information, gain social and economic benefits, makes it easier for us to interact with many people, expand relationships, distance and time are no longer a problem. It has been more than a year that this pandemic has changed the order of people’s lives in Indonesia. So that many places of business do not develop, and many end up in bankruptcy. All activities are carried out onlie to avoid gathering people in various places. The current pandemic is engulfing various parts of the world, including Indonesia, causing various impacts on people’s lives, especially in the economic field (many have gone out of business, many have been laid off, and others). Therefore, the purpose of this paper is to find out the role of social media during the pandemic for the progress fo the community’s economy. The results of this paper indicate that social media can play a role in restoring the community’s economy, and become an alternative during this pandemic. This study uses a literature review method, with data collection techniques via the internet, journals and books related to the theme.